Analisis Dasar Pertimbangan Hakim Dan Akibat Hukum Dalam Menolak Gugatan Cerai Yang Tidak Dapat Diterima (Niet Ontvankelijke Verklaard) Di Pengadilan Dilihat Dari Perspektif Hukum Acara Perdata - Raynaldo Handojo Putra; Mia Hadiati (UNES Law Review, 2023)
This research aims to carry out an in-depth analysis of the judge's basic considerations and legal consequences in rejecting an unacceptable divorce claim (niet ontvankelijk verklaard) in court, seen from the perspective of Civil Procedure Law. This study explores various legal aspects that form the basis of a judge's consideration in rejecting a divorce lawsuit and the legal implications for the parties involved. The research method used involves legal text analysis, case studies, and a comparative legal approach to understand the legal framework that supports the judge's decision to reject an unacceptable divorce lawsuit. The results of this research provide in-depth insight into the legal process involving judge deliberations in this context and its impact on both parties